Live Coding the Communication Complexity Scale: Validation of a Clinically Relevant Observation Tool - Mancini, Jordana (ProQuest Dissertations & Theses, 2020)
In this preliminary research study, the effect of live scoring versus video scoring of the observational rating tool, the Communication Complexity Scale (CCS), was examined through three participant variables and one assessment variable: communication level of the participant, age of the participant, severity of autism of the participant, and assessment task function (joint attention or behavior regulation). Participants included 42 children between three and 18 years of age, who were referred by special educators in the suburban Kansas City, KS and Lawrence, KS school districts. Children were administered a 30-minute, scripted play-based assessment which used “sabotaged” games or toys to promote communication of the research subjects. The CCS was used to score the assessment by a live coder, as well as a video coder at a delayed time. Through analysis conducted in this study, it was found that there was not a significant difference when applying the CCS as an observational tool regardless of the participants communication level, age, severity of autism, nor the function of the task assessed by the scripted play-assessment. In clinical application, it was found that live and video scoring are both methodologically sound mediums to apply the CCS, which can be used based on clinician or client preferences or needs.